Is intensive care necessary after elective abdominal aortic aneurysm repair? - Lawlor, D. Kirk (Canadian Medical Association, 2004)
BACKGROUND: To review morbidity and mortality of patients undergoing elective, open repair of infrarenal abdominal aortic aneurysms and were admitted postoperatively to a surgical stepdown unit rather than routinely to the intensive care unit (ICU), we carried out a retrospective review. METHODS: All patients undergoing this type of repair in our centre, a division of vascular surgery in a tertiary-care teaching hospital in Ontario, over a 27-month period were reviewed. A consecutive 230 patients who underwent aneurysm repair from September 1999 through November 2001 were routinely admitted to a surgical stepdown unit postoperatively, with only a minority of patients requiring admission to ICU. We reviewed the rate of initial ICU admission and that of subsequent ICU admission after stepdown-unit admission. We also assessed morbidity, mortality and length of hospital stay for patients admitted to ICU as well as those admitted to the stepdown unit. RESULTS: ICU admission was avoided in 204 (89%) of these patients. The remaining 26 patients (11%) required ICU admission at some point during their hospital stay. Only 3 patients (1%) originally admitted to the stepdown unit subsequently required postoperative admission to ICU. CONCLUSIONS: Our experience demonstrates that proper preoperative assessment and selection allows the majority of elective infrarenal aneurysm repairs to be safely cared for postoperatively in a stepdown unit, and that subsequent ICU admissions are rare.